Assessing cropping systems and mustard varieties for enhanced system yield and profitability: strategies for climate resilience in arid Western Rajasthan - Lal Reager, Madan; Singh Kherawat, Bhagwat; Gawdiya, Sandeep; Kishor, Naval; Jatav, Hanuman Singh; Pant, Richa; Kumari, Kiran; Ram Raiger, Prahlad; Choudhary, Anirudh; Mattar, Mohamed A.; Salem, Ali (Frontiers in Sustainable Food Systems, 2025)
ContextMustard (Brassica juncea L.) is a major oilseed crop in India, particularly suited to arid and semi-arid regions like Rajasthan, where low soil fertility, erratic rainfall, and limited irrigation resources constrain productivity. Diversifying cropping systems with legumes and selecting suitable mustard varieties are essential strategies for improving system productivity, enhancing resource use efficiency, and ensuring sustainable oilseed production in dryland agro-ecosystems.ObjectiveThis study aimed to evaluate the interactive effects of preceding crops and mustard varieties on system productivity, profitability, and land-use efficiency under arid conditions. The specific goals were to (i) assess the impact of kharif-season crops on mustard growth and yield, (ii) compare varietal performance across cropping systems, and (iii) identify optimal system–variety combinations for maximizing economic returns and resource-use efficiency.MethodsA two-year field experiment (2021–22 and 2022–23) was conducted on loamy sand soils in Rajasthan using a split-plot design with three replications. The main plots included seven cropping systems: fallow-mustard, groundnut-mustard, sesame-mustard, cluster bean-mustard, green gram-mustard, moth bean-mustard, and pearl millet-mustard. Five mustard varieties (RGN-145, RGN-236, RH-749, DRMRIJ-31, and RH-725) were assigned to sub-plots. System productivity was evaluated using mustard equivalent yield (MEY and MESY), grain and straw yield, production efficiency, land resource use efficiency, net returns, and benefit–cost ratio (B:C). Significance was tested at p < 0.05.ResultsSignificant differences were observed among cropping systems and mustard varieties for all measured indicators. The cluster bean-mustard system combined with RH-725 achieved the highest grain yield (1.95 t ha−1), straw yield (5.24 t ha−1), net returns (₹124,317 ha−1), and B: C ratio (4.55). In contrast, RGN-145 under the groundnut-mustard system produced the highest grain yield (2.21 t ha−1), net returns (₹238,147 ha−1), and B:C ratio (4.27) among all combinations. Additionally, RGN-145 and RGN-236 under the groundnut-mustard system recorded the highest mustard equivalent yield (MEGY), stover yield (MESY), and land-use efficiency, indicating their suitability for system intensification.ConclusionLegume-based cropping systems, particularly groundnut-mustard and cluster bean-mustard, significantly improved mustard productivity and profitability in arid environments. Their integration with high-performing varieties such as RGN-145 and RH-725 offers a viable pathway for sustainable intensification, improved soil health, and climate-resilient mustard production in dryland farming systems.